2021
DOI: 10.3390/ijerph18031127
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and Panic Buying Behaviour during COVID-19 Pandemic—A Qualitative Analysis of Toilet Paper Hoarding Contents on Twitter

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic had increased population-level anxiety and had elicited panic buying behaviour across the world. The over-hoarding of toilet paper has received a lot of negative public attention. In this work, we used Twitter data to qualitatively analyse tweets related to panic buying of toilet paper during the crisis. Methods: A total of 255,171 tweets were collected. Of these 4081 met our inclusion criteria and 100 tweets were randomly selected to develop a codin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 24 publications
5
67
1
2
Order By: Relevance
“…Another study, using structural equation models, revealed that cyberchondria—that is, excessive information gathering about COVID-19 combined with feelings of frustration and anxiety—is positively associated with the intention to make unusual purchases [ 38 ]. A qualitative study on contents on twitter about toilet paper hoarding found out that nearly half of the analyzed tweets expressed negative feelings toward panic buying [ 39 ]. The authors hypothesize that this might lead to emotional distress, depression and anxiety-driven panic buying (see also [ 40 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Another study, using structural equation models, revealed that cyberchondria—that is, excessive information gathering about COVID-19 combined with feelings of frustration and anxiety—is positively associated with the intention to make unusual purchases [ 38 ]. A qualitative study on contents on twitter about toilet paper hoarding found out that nearly half of the analyzed tweets expressed negative feelings toward panic buying [ 39 ]. The authors hypothesize that this might lead to emotional distress, depression and anxiety-driven panic buying (see also [ 40 ]).…”
Section: Discussionmentioning
confidence: 99%
“…The burgeoning evidence on panic buying globally due to COVID-19 shows that stockpiling behavior of non-perishable food and bathroom products was not uncommon, with panic buying of toilet paper receiving considerable media publicity (Garbe et al 2020;Kirk and Rifkin 2020;Loxton et al 2020;Yoshizaki et al 2020;Leung et al 2021;Taylor 2021). Panic buying is part of the wider process of consumption displacement that occurs during disasters and pandemics.…”
Section: Panic Buying and Consumption Displacement During Covid-19mentioning
confidence: 99%
“…Hoarding or stockpiling is the act of collecting and safeguarding a large quantity of possessions for future use (Chu 2018). Consumer hoarding during COVID-19 were likely to be primarily affected by government public health interventions that served to constrain consumers' normal consumption behaviors and practices (Hall et al 2020), e.g., in terms of where, when and how to purchase; supply chain disruptions (Kirk and Rifkin 2020;and social media (Zhao and Zhou 2020;Leung et al 2021), and sensationalist media reporting (Arafat et al 2020b). This was manifested by product scarcity on shelves, most recognizably with respect to a seeming global concern with the availability of toilet paper (Garbe et al 2020;Loxton et al 2020;Yoshizaki et al 2020;Leung et al 2021;Taylor 2021), and aggressive instore consumer behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Access to prescribed medications is important in reducing morbidity for people with diabetes [ 8 ]. While the pandemic has led to panic buying and subsequent shortages of consumer goods like toilet paper [ 9 , 10 ] and minced meat [ 11 , 12 ], it is unclear what impact a global pandemic may have on diabetes medication demand across the world. Australia offers an opportunity to study this, with readily available dispensed medicines data and is of interest as it imports over 90% of medicines—hence is highly dependent on global supply chains [ 13 ].…”
Section: Introductionmentioning
confidence: 99%